Preparation and Characterization of Cellulose Composite Hydrogels From Tea Residue and Single-Walled Carbon Nanotube Oxides and Its Potential Applications - Liu, Zhijun; Li, Dianxin (Frontiers in Chemistry, 2021)
Hydrogels were prepared from tea cellulose with the addition of single-walled carbon nanotube oxide by mixing in 1-allyl-3-methylimidazolium chloride. The single-walled carbon nanotube oxide/tea cellulose hydrogels were characterized by Fourier transform infrared, X-ray diffraction, texture profile analysis, and thermogravimetry analysis. The adsorption capacity of methylene blue by the prepared hydrogels was also investigated. The hydrogels exhibited higher thermal stability and intensive textural property with the addition of single-walled carbon nanotube oxide. As comparison to the undoped tea cellulose hydrogel, the weight loss peak moved from 280 °C to 323 °C, and the values of hardness, fracturability, gumminess and resilience were 8.4, 5.3, 10.8 and 1.9 times of tea cellulose hydrogels (TCH) respectively. As an absorbent of methylene blue, the single-walled carbon nanotube oxide/tea cellulose hydrogels accorded to pseudo-second-order kinetic model, good adsorption capacity (13.80 mg/g) and adsorption ratio (27.59%), and showed potential in drug carrier.